2018
DOI: 10.1016/j.enbuild.2018.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Building energy simulation coupled with CFD for indoor environment: A critical review and recent applications

Abstract: This paper presents a comprehensive review of the open literature on motivations, methods and applications of linking stratified airflow simulation to building energy simulation (BES). First, we review the motivations for coupling prediction models for building energy and indoor environment. This review classified various exchanged data in different applications as interface data and state data, and found that choosing different data sets may lead to varying performance of stability, convergence, and speed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(53 citation statements)
references
References 63 publications
0
51
1
1
Order By: Relevance
“…Although this does not reflect physical reality well, the only current alternative is computational fluid dynamics (CFD)-a complex and computationally intensive simulation of air movement (Crawley et al 2001). Several studies have shown that the improvement in modeling accuracy from using CFD for building energy simulations is negligible compared to the increase in time and computational power required to run such models (Martinet al 2017;Tan & Glicksman 2005;Tian et al 2018;Zhai et al 2002). CFD models look at the thermal zone at a discretized level by breaking it into large amounts of control volumes, which is not useful for running annual simulations of the whole building (Martin et al 2017).…”
Section: Modeling Thermal Bridging and Infiltrationmentioning
confidence: 99%
“…Although this does not reflect physical reality well, the only current alternative is computational fluid dynamics (CFD)-a complex and computationally intensive simulation of air movement (Crawley et al 2001). Several studies have shown that the improvement in modeling accuracy from using CFD for building energy simulations is negligible compared to the increase in time and computational power required to run such models (Martinet al 2017;Tan & Glicksman 2005;Tian et al 2018;Zhai et al 2002). CFD models look at the thermal zone at a discretized level by breaking it into large amounts of control volumes, which is not useful for running annual simulations of the whole building (Martin et al 2017).…”
Section: Modeling Thermal Bridging and Infiltrationmentioning
confidence: 99%
“…Comprehensive review of the literature regarding the coupled simulation of building energy systems and the indoor environment (Tian et al, 2018) indicates that the previous studies only focused on the integration of air handler units with indoor environment, whereas none of these studies ever took into account the dynamics of vapor compression systems, which are the essential part of building HVAC systems through which heat is removed from or added to buildings. Also, they are the primary energy consumer compared to other auxiliary components, such as pumps and fans.…”
Section: 3384/ecp19157265mentioning
confidence: 99%
“…Sustainability has become a significant factor in the building sector [1][2][3], integrating such aspects as design, construction, rehabilitation and operation. In the field of building simulations, researchers are looking for new information to obtain a more efficient building depending on the location and its climatology [4][5][6], and thus make energetic savings.…”
Section: Introductionmentioning
confidence: 99%